用于辅助诊断AD的多频脑网络区分子网络对的构建方法 (2023)
本发明公开了一种用于辅助诊断AD的多频脑网络区分子网络对的构建方法，属于计算机辅助诊断技术领域。将包含AD和NC的fMRI数据集中大脑各感兴趣区域的时间序列信号分为多个频段；计算同一频段内任意两感兴趣区域的相关系数；对相关系数进行阈值化构建每一被试的多频脑网络，获得AD和NC两个多频脑网络数据集并进行频繁子网络挖掘得到两个多频频繁子网络集；分别计算两个多频频繁子网络集中各子网络的区分能力并从两者中分别取能力最强的前若干个子网络进行组合构建各频段的子网络对即区分子网络对；计算区分子网络对的差异度，并取每个频段差异度最大的前k个区分子网络对按照差异度降序排序，选择前k'个子网络对作为用于辅助诊断AD的的区分子网络对。 The invention discloses a construction method of a multi-frequency brain network area molecular network pair for auxiliary diagnosis of AD, and belongs to the technical field of computer-aided diagnosis. The method comprises the steps of dividing time sequence signals of each region of interest of the brain in the fMRI data set containing AD and NC into a plurality of frequency bands; calculating a correlation coefficient of any two regions of interest in the same frequency band; performing thresholding on the correlation coefficients to construct a multi-frequency brain network of each subject, obtaining an AD multi-frequency brain network data set and an NC multi-frequency brain network data set, and p